110 Is Type 1 Diabetes Mellitus Associated With Lower Limb Tendon Pathology? A Systematic Review. (5th September 2014) - Wong, Andrea MY; Docking, Sean I; Cook, Jill L; Gaida, James E
Abstract : Introduction: Type 1 diabetes mellitus (T1DM) occurs when insulin-producing cells are destroyed by an autoimmune response, resulting in hyperglycaemia. Hyperglycaemia accelerates collagen cross-linking in tendons, which can deteriorate tendon structure and predispose to tendon injury (Reddy 2003). Tendon pathology has been observed in the type 2 DM (T2DM) population (Akturk et al . 2007; Papanas et al . 2009), however little is known about T1DM and tendon pathology. This review examines whether there is an association between T1DM and lower limb tendon pathology. Methods: Five databases were comprehensively searched for English language journal articles that reported on three key domains: (i) T1DM, (ii) lower limb, and (iii) tendon pathology. Reference lists of included studies or reviews were manually inspected for relevant papers. Articles were excluded if they were: case reports; animal models; conference abstracts; or did not provide T1DM data. Results: The search yield of 593 papers was evaluated by title and abstract and 38 papers were read in full text. Only one article met all inclusion criteria (Figure 1 ). Three potentially eligible articles pooled tendon outcome data for T1DM and T2DM individuals (Bolton et al . 2005; D'Ambrogi et al . 2005; Giacomozzi et al . 2005). Original data was sought from the authors, but was no longer available. The one included article was a cross-sectional study that reported the prevalence of T1DM among individuals with midportion Achilles tendinopathy. This study reviewed electronic medical records from GP practices in the Netherlands, where all reasons for visit are recorded on a computerised registration system. The prevalence of T1DM in those with Achilles tendinopathy (1.8%, 95% CI, 0 to 4.5) was the same as in the general Dutch population (0.8%, CI, NA) (de Jonge et al . 2011). Discussion: The main finding of this review was no difference in the prevalence of T1DM between individuals with tendinopathy and the general population. The review highlighted two other key points: (i) there is very limited published data on tendon pain or structure in T1DM, and (ii) despite profound difference in T1/T2DM pathophysiology and co-morbidities, data are commonly combined. Articles that pooled T1DM and T2DM tendon data did not meet the review inclusion criteria. An effort was made to obtain original T1DM data, which was unsuccessful. These studies found DM individuals had significantly thicker Achilles tendons (p < 0.05) (D'Ambrogi et al . 2005; Giacomozzi et al . 2005), but similar flexor hallucis longus tendon thickness (p > 0.05) (Bolton et al . 2005) compared to controls. However, the influence of T1DM on tendon structure in these studies is unknown. The interest in investigating T1DM and T2DM separately comes from the differing pathophysiological causes of DM and exposure to hyperglycaemia. Other characteristics more specific to T2DM may predispose tendons to pathological changes, such as insulin resistance (Gaida et al . 2009b), elevated lipids (Beeharry et al . 2006) and adiposity (Gaida et al . 2009a). References: Akturk et al . Exp clin endocrinol. 2007;115:92–6 Beeharry et al . Ann Rheum Dis. 2006;65:312–5 Bolton et al . Clin Biomech. 2005;20:540–6 D'Ambrogi et al . Diabetic Med. 2005;22:1713–9 de Jonge et al . Brit J Sport Med. 2011;45: 1026–8 Gaida et al . Arthritis Rheum. 2009a; 61:840–9 Gaida et al . Med Sci Sport Exer. 2009b; 41:1194–7 Giacomozzi et al . Clin biomech. 2005;20:532–9 Papanas et al, Exp clin endocrinol. 2009;117:645–8 Reddy, J Orthopaed Res. 2003;21:738–43